Militanza, “impegno” e critica sociale dell’antropologia sulla base di intense etnografie. Le intenzioni trasformative e i giudizi politici dell’antropologo - Antonino Colajanni (Archivio Antropologico Mediterraneo)
The essay is devoted to an historical analysis of the progressive engagement of anthropological studies on the contemporary world with its difficult and conflictual situations. A particular attention is dedicated to the possible relations between anthropological studies and the different forms and aspects of power and the social action devoted to the transformation of the social and political relations. Starting from a brief analysis of the main responsibilities of anthropology in the colonial era, a particular attention is devoted to the origins and developments of the american orientation of the “engaged anthropology”, from the late years ’70. The themes and objects of research on that period changed drastically from the previous academic traditions, and social conflicts, wars, forms of violence, feminism, environmental crisis, have been identified as the ordinary problems to be studied. A following analysis is devoted to the intensive debate, diffused in Italy in the last decade, on an essay by Fabio Dei on the objections to the “radical critics to the State as an example of diffused and constrictive power”; and a specific attention is dedicated to an interesting book on the “militant anthropology”. Then, some concluding remarks are proposed on the necessity of an intensive and long-time ethnographic research for an acceptable form of “engaged anthropology”. The essay ends with a reference to some examples of “soft-engagement” by the author within its ethnographic researches in various contexts of indigenous South America.